Peran Kalsium (Ca) dan Calmodulin (CaM) Dalam Mekanisme Adaptasi Tanaman Terhadap Cekaman Lingkungan - Robiatul Adawiyah; Namriah Namriah (University of Halu Oleo, 2019)
Abstract.The availability of fertile lands for agriculture is going decrease due to the pressure of housing and industrial interests. These problems force the development of agricultural businesses should lead to the use of problematic land (marginal) with various environmental stress problems. Marginal land includes dry land, acid land and land affected by salt. One alternative in supporting efforts to increase food crop production on marginal land is the use of tolerant crops. Tolerant plants are strongly related to the role of calcium (Ca) and calmodulin (CaM, calcium modulated protein), which is a functional protein in cells. The performance of Ca2 + -Calmodulin in regulating plant adaptation to environmental stress can be through two possibilities, namely: Ca2 + -Calmodulin can cause physical strength of plants through plant membrane integrity and Ca2 + -Calmodulin can affect plant physiology activities through its influence on metabolic activity, ion balance in cytoplasm, growth regulator hormone activity and protein modification arrangements. With increasing membrane stability, plants are able to adapt to environmental stresses. Stimulation from the environment will activate gene expression and metabolic activity, thus giving rise to the tolerance of plants to environmental stress. Keywords : calcium, calmodulin, environmental stress, adaptation mechanism